Francine Poulet Meets the Ghost Raccoon - DiCamillo, Kate.; Van Dusen, Chris (Somerville, Massachusetts : Candlewick Press, 2015)
When she confronts a screaming raccoon that may or may not be a ghost, animal control officer Francine Poulet questions her abilities.
"A Junior Library Guild selection"--Jacket flap.
Accelerated Reader AR
Keywords: Animal welfare -- Juvenile fiction; Dangerous animals -- Juvenile fiction -- Control; Raccoon -- Juvenile fiction; Fear -- Juvenile fiction